Synthesis and Characterization of New D-π-A Type Fluorene Ligands and Their Ru(II) Complexes - Erden, Ibrahim; Kilicarslan, Fatma Aytan; Erdogmus, Ali (TAYLOR & FRANCIS INC, 2015)
4,5-Diazafluorene ligands, (L1) and (L2), have been synthesized from the reaction of 4,5-diazafluorenone-9-hydrazone with 4-(4-fluorophenoxy) benzaldehyde and 4,5-diazafluoren-9-one with 4-(4-fluorophenoxy) benzylamine hydrochloride in dry EtOH. Ru(II) complexes of the ligands Ru(II)-L1 and Ru(II)-L2 were prepared by treating the ligands with Ru(bpy)(2)CI2 in dry EtOH. The metal-to-ligand ratio of the Ru(II) complexes was found to be 1:1. The ligands and complexes were characterized by elemental analysis and spectra FTIR, UV-vis, H-1 NMR, MS, and fluorescence studies.
Keywords: 4,5-diazafluorene; Schiff base; D-pi-A; HIGH-EFFICIENCY; ORGANIC-DYES; Chemistry; Science & Technology - Other Topics